PERENCANAAN STRATEGIS SISTEM INFORMASI PUSAT KESEHATAN PESANTREN BERBASIS TOGAF ADM UNTUK MENDUKUNG TRANSFORMASI DIGITAL - Akhlis Munazilin; Siti Imroatul Janna; Rizqi Tussarifa (Jurnal Riset Teknik Komputer, 2026)
Islamic boarding school health centers play a strategic role in providing healthcare services for students and the surrounding community. However, the patient registration process is still largely conducted manually, leading to various problems such as service delays, data recording errors, and difficulties in managing and tracing patient medical histories. These conditions indicate the need for a system that is able to improve efficiency, accuracy, and overall service quality. This study aims to design an Enterprise Architecture for a web-based patient registration information system integrated with Radio Frequency Identification (RFID) technology using the TOGAF (The Open Group Architecture Framework) with the Architecture Development Method (ADM) approach. The research adopts a qualitative-descriptive method through observation, interviews, and documentation studies to identify system requirements and existing business process problems. The results of this study are presented in the form of an architectural blueprint that includes business architecture, data architecture, application architecture, and technology architecture. The proposed business architecture transforms the registration process from a manual system into a digital one by utilizing RFID cards as an automatic patient identification medium. The data and application architectures are designed to support integrated patient data management, while the technology architecture focuses on the use of a web-based system, a centralized database, and RFID devices as the main operational support. The findings indicate that the implementation of Enterprise Architecture based on TOGAF ADM combined with RFID technology is able to improve the efficiency of the registration process, minimize data entry errors, accelerate service delivery, and enhance the security and availability of patient information. Therefore, the blueprint produced in this study can serve as a strategic reference for the development and implementation of an integrated information system in Islamic boarding school health centers.